2003
DOI: 10.1021/bi034541n
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Chaperone Function of α-Crystallin by Methylglyoxal Modification

Abstract: The molecular chaperone function of alpha-crystallin in the lens prevents the aggregation and insolubilization of lens proteins that occur during the process of aging. We found that chemical modification of alpha-crystallin by a physiological alpha-dicarbonyl compound, methylglyoxal (MG), enhances its chaperone function. Protein-modifying sugars and ascorbate have no such effect and actually reduce chaperone function. Chaperone assay after immunoprecipitation or with immunoaffinity-purified argpyrimidine-alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
120
4
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 50 publications
5
120
4
3
Order By: Relevance
“…However, to date, the impact of these modifications on the chaperone ability of sHsps to prevent amyloid fibril formation has not been investigated. This area of study is significant since these post-translational modifications occur to a significant extent to the crystallin proteins in the eye lens [12, [127][128][129][130][131][132][133]. There is increasing evidence that cataract may be an amyloid fibril based disease (see below) and, as such, the impact of such modifications on the chaperone ability of α-crystallin to prevent this process is highly relevant.…”
Section: The Effect Of Post-translational Modifications On the Chapermentioning
confidence: 99%
“…However, to date, the impact of these modifications on the chaperone ability of sHsps to prevent amyloid fibril formation has not been investigated. This area of study is significant since these post-translational modifications occur to a significant extent to the crystallin proteins in the eye lens [12, [127][128][129][130][131][132][133]. There is increasing evidence that cataract may be an amyloid fibril based disease (see below) and, as such, the impact of such modifications on the chaperone ability of α-crystallin to prevent this process is highly relevant.…”
Section: The Effect Of Post-translational Modifications On the Chapermentioning
confidence: 99%
“…In the retina of experimental autoimmune uveitis-induced mice, several proteins including alphaA-crystallin and mitochondrial Hsp70 were targeted by posttranslational modifications [63]. Chemical posttranslational modification of alpha-crystallins and Hsp27 by a metabolic product, methylglyoxal (MG), has been shown to enhance their chaperone function [64]. In the retinal epithelial cells, it has been concluded that S-glutathionylation of Hsc70 enhances its chaperone function, allowing it to prevent protein aggregation in ATP-free conditions [65].…”
Section: Regulation Of Functionmentioning
confidence: 99%
“…Besides the reducing sugars, α-dicarbonyl compounds like methylglyoxal or glyoxal which arise during glycolysis (Nagaraj et al 2003;Ghosh et al 2006), fatty acid degradation and autoxidation of glucose (Fu et al 1998) can react with free amino acid groups of endogenous proteins and contribute to AGE-formation. Food contains large quantities of Maillard reaction products (MRPs) or AGEs which arise during heating and processing and contribute to the characteristic flavour and colour.…”
Section: Introductionmentioning
confidence: 99%